2015
DOI: 10.3758/s13421-015-0580-9
|View full text |Cite
|
Sign up to set email alerts
|

Recalling visual serial order for verbal sequences

Abstract: We report three experiments in which participants performed written serial recall of visually presented verbal sequences with items varying in visual similarity. In Experiments 1 and 2 native speakers of Japanese recalled visually presented Japanese Kanji characters. In Experiment 3, native speakers of English recalled visually presented words. In all experiments, items varied in visual similarity and were controlled for phonological similarity. For Kanji and for English, performance on lists comprising visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 55 publications
4
71
3
Order By: Relevance
“…These, and related (Logie, Saito, Morita, Varma, & Norris, 2015;Saito, Logie, Morita, & Law, 2008) studies have produced mixed findings, with some authors arguing for domain-specific ordering of verbal vs. visuo-spatial information while accepting that these two mechanism operate on very similar principles (Logie et al, 2015;Hurlstone et al, 2014). However, the current balance of evidence appears to be in favour of at least some degree of domain-general short-term ordering of representations (see Farrell & Oberauer, 2014;Vandierendonck, 2016).…”
Section: Working Out How 21mentioning
confidence: 82%
“…These, and related (Logie, Saito, Morita, Varma, & Norris, 2015;Saito, Logie, Morita, & Law, 2008) studies have produced mixed findings, with some authors arguing for domain-specific ordering of verbal vs. visuo-spatial information while accepting that these two mechanism operate on very similar principles (Logie et al, 2015;Hurlstone et al, 2014). However, the current balance of evidence appears to be in favour of at least some degree of domain-general short-term ordering of representations (see Farrell & Oberauer, 2014;Vandierendonck, 2016).…”
Section: Working Out How 21mentioning
confidence: 82%
“…Similarly, the overall effect of presentation modality, observed in the main analysis of the Logie et al (1996) data presented above, could well reflect the fact that visually presented material can potentially be encoded and retained in a non phonological form, which might be less effective than phonological coding for retaining serial order (Logie, Della Sala, Wynn & Baddeley, 2000;Logie et al, 2015;Saito et al, 2008). Warrington and Shallice (1972) reported that the brain-damaged patient, KF, only showed a severe verbal short-term memory deficit with auditory presentation.…”
Section: Discussionmentioning
confidence: 94%
“…In other words, although visual presentation led to a significantly smaller absolute effect of similarity than auditory presentation, this can be entirely accounted for statistically by the fact that baseline levels of recall were smaller in the visual presentation condition as shown above. This leaves open the question of whether the smaller visual presentation effect reflects the reduced ability of visual coding to retain serial verbal order (e.g., Logie, Saito, Morita, Varma, & Norris, 2015;Saito, Logie, Morita & Law, 2008) or impaired phonological loop functioning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations